Water depth‐dependent notonectid predatory impacts across larval mosquito ontogeny. Issue 10 (13th March 2019) - Dalal, Arpita; Cuthbert, Ross N; Dick, Jaimie TA; Gupta, Susmita
Abstract: BACKGROUND: Context‐dependencies can modulate the strength of predatory interactions and often remain unquantified. In particular, differences in water depth within aquatic systems could influence predator efficiencies towards prey which utilise three‐dimensional space through the water column. Differences in prey size could drive prey size–refuge effects, influencing the efficacy of natural enemies towards vector species. We thus quantify the predatory impact of two notonectid predators, Anisops breddini and Anisops sardeus, towards four different larval instars of Culex quinquefasciatus prey across a water depth gradient, using functional responses (FRs). RESULTS: Consumption rates differed significantly between the predators, and interspecific differences in responses to variations in water depth were emergent. Both notonectids were able to handle C. quinquefasciatus prey across all instar stages, yet predation rates were generally higher towards early as opposed to late instar prey. Anisops sardeus was most voracious, and differential predation rates of this species were most pronounced in shallow waters. Type II FRs were displayed by notonectids in the majority of treatments; however, Type III FRs were emergent in specific treatment groups, with potential implications for prey population stability. Both capture rates and handling times were often greater at greater depths, and thus maximum feeding rates reduced as depth increased. Our results further demonstrate substantial predatory impacts of notonectid predators towards mosquito, and quantify biotic and abiotic context‐dependencies which modulate their impact. CONCLUSION: Given notonectids are capable of aerial dispersal between ephemeral aquatic habitats of varied volumes, their promotion in aquatic systems could help reduce proliferations of medically important mosquitoes. © 2019 Society of Chemical Industry Abstract : Notonectids are an important biocontrol agent of mosquito larvae in a container‐style habitat feeding all the prey instars across three water depth levels. Interspecific differences were emergent with changing water depth.